Granular Cell Tumor of the Pituitary Stalk: A Rare and Benign Entity. Issue 1 (15th September 2015) - Gregoire, A.; Bosschaert, P.; Godfraind, C.
Granular cell tumor of the pituitary stalk is an uncommon benign lesion that usually appears like a suprasellar mass with visual disturbances. This diagnosis should be considered with the discovery of neurohypophysis tumors. Histological confirmation remains essential. We describe one case of this rare entity and review the literature.